Cross Reaction of Serum in Salmonella enteritidis- Vaccinated Chicken to Some Salmonella enterica Serotypes (REAKSI SILANG SERUM AYAM YANG DIVAKSIN DENGAN SALMONELLA ENTERITIDIS TERHADAP BEBERAPA SEROTIPE SALMONELLA ENTERICA) - Arnafia, Wyanda; Ningrum, Siti Gusti; Puspita, Erfiandini Eka; Lukman, Denny Widaya; Pasaribu, Fachriyan Hasmi; Wibawan, I Wayan Teguh (Jurnal Veteriner; Vol 17 No 3 (2016), 2016)
Salmonella spp. has been recognized as the major cause of food-borne illness in humans worldwidecausing remain relevant to public health. Poultry vaccination is one promising strategy to mitigateSalmonella infection in poultry and, in turn, in humans as well. The objective of this study was to assessthe potential of cross-reaction of serum in Salmonella enteritidis-vaccinated chicken to some serotype ofSalmonella enterica. Four female, Isa Brown layer chickens (20 weeks old), were vaccinated with S. enteritidisstrain Sm24/Rif12/Ssq (intra vena) to induced the production of specific antibodies in serum. Crossreactionof serum in S. enteritidis-vaccinated chicken were assess with agar gel immunodiffusion test(AGID) with S. enteritidis, S. pullorum, S. typhimurium, S. typhi, and Escherichia coli antigens. Serumcould react with S. enteritidis and all types of S enterica used in this study (S. pullorum, S. typhimurium,S. typhi), but could not react with E. coli. The potential of cross-reaction of serum in S. enteritidis-vaccinatedchicken to some serotypes of S. enterica may play a role in reducing the infection caused by that serotype.
Keywords: Salmonella enteritidis; Salmonella enterica; cross-reaction